Факторы влияющие на динамику качества жизни после хирургического лечения расслоения восходящего отдела и дуги аорты - O. V. Kamenskaya; A. S. Klinkova; I. Yu. Loginova; A. M. Chernyavsky; V. V. Lomivorotov; A. M. Karaskov (Российский кардиологический журнал, 2018)
Aim. To assess the impact of clinical and intraoperative factors on the dynamics of quality of life (QOL) after aortic prosthetics in patients with chronic dissection of ascending aorta and aortic arch.Material and methods. The study included 56 patients (mean age 50 years) with chronic DeBakey type I aortic dissection. With the help of the SF36 questionnaire, QOL was examined before and later (12 months) after aortic prosthetics. The method of multivariate linear regression analysis was used to evaluate factors that influence the dynamics of various parameters of QOL in the late postoperative period. Results. Before the operation, patients scored from 52 points and below almost in all parameters of the questionnaire, which indicates a very low initial level of QOL. In the longterm period after aortic prosthetics, a statistically significant improvement in the following physical and psychoemotional indicators was noted: role functioning (p=0,004); bodily pain (p=0,0001); vitality (p=0,009); social role functioning (p=0,002); emotional role functioning (p=0,009); physical health (p=0,02); mental health (p=0,03). At the same time, there was no positive change in the initial low parameters of general health and psychiatric health perceptions.According to multivariate regression analysis, the dynamics of QOL parameters in the longterm period after surgical treatment of the dissection of ascending aorta and aortic arch are affected by both intraoperative conditions (cerebral protection method) and the early postoperative period (neurological complications, cardiopulmonary failure, atrial fibrillation). Indicators such as gender, age, body weight, comorbidity, type of prosthesis of the ascending aorta, time spent in the intensive care unit, duration of artificial pulmonary ventilation do not have a significant effect on QOL in the longterm postoperative period.Conclusion. Clinical and intraoperative factors that adversely affect the dynamics of various indicators of QOL in longterm periods after prosthetics of the ascending aorta and aortic arch were: cerebral protection in conditions of deep hypothermia and craniocerebral hypothermia against the background of systemic circulatory arrest; development of neurological complications, as well as atrial fibrillation and cardiopulmonary failure in the early postoperative period.